PC sound card based instrumentation and control - Gunawan, Teddy Surya (IIUM Press, 2011)
The availability of inexpcnsivc PC sound cards that can simultaneously play and rcrord stereo digital audio files pennits a single PC OT laptop or netbook to function as both a signal generator and as a dual-channel recording digital oscilloscope. This paper presents how sound card with Matlab Data Acquisition Toolbox can be utili7.ed for inSlrumcntation and control. Th~ buff~r hardware circuit or signal conditiooillg circuit is developed and implemellted to enablc sound card to be functioned like oscilloscope. Preliminary results showed that sound card with the developed software has a good potential fOT instnllTlentation and control